PENGARUH LAMA PENGERINGAN DAN BERBAGAI JENIS GULA TERHADAP KUALITAS MANISAN TOMAT (LYCOPERSIUM ESCULENTUM) - Febriyanti, Nurul; Caronge, Muhammad Wiharto; Lahming, Lahming (Universitas Negeri Makassar, 2018)
The purpose of this research is to know the influence for a long time drying and various types againts sugar used to the quality of candied tomatoes. This research uses a factorial completely randomized design consisting of two factors, factor A is the type of sugar (granulated sugar and brown sugar) and the B factor is drying (10, 12 and 14 hours) which done with 2 treatments and 3 time repetitions. The research variables observed were organoleptic test, water content and vitamin C level. The analysis technique used in this research was analysis of variance analyzed by using SPSS version 20.0. The results showed the is best treatment the use of brown sugar with 14 hours drying time with the best quality determinant indicator was based on water content test parameter (22,73), vitamin C content (0,177) and organoleptic tests include , color (3,36), taste ( 3.30), aroma (3.55), texture (3,46).